Patterns and Trends of Out-migration in Syangja District of Nepal - Parajuli, Chandra; Naupane, Bibek K.; Khatri, Bishnu B.; Koirala, Arjun (Ganeshman Darpan, 2023)
When migration occurs, it has a significant impact on the lives and livelihoods of individuals, communities, societies, and the nation. In this regards, the paper aims to examine the patterns and trends of out-migration in Syangja district of Nepal. As key data sources, government records, Nepal Census Data 2021, and related reports were used for analysis. This research has employed a descriptive research approach for the analysis of the trends and patterns of migration in Syangja district. On the basis of secondary data, the information on the population growth, migration pattern and trend, causes of migration, and the preferred destination has been presented and discussed. The article has also discussed the factors influencing decisions on migration. The study reveals that people of Syangja had chosen to migrate both within the country and outside. The main reasons for migration were primarily employment and education, which is considerably lacking in Syangja. The findings indicate that migrants expect a higher standard of living as a result of their migration. Understanding the migration patterns and trends which are helpful for the policymakers and decision makers to formulate the district specific policy and strategy as well as to regulate and harness the benefits of migration.